永磁齿轮传动特性影响因素分析 - 刘继超; 曹家勇; 刘洋 (Jixie chuandong)
Based on calculation and analysis of permanent magnetic gears with parallel axis using two-dimensional finite element method,the influence of the number of magnetic poles,air gap and the radiuses of gears exerting on the torqueangle curve is studied.Comparison of torque-angle curves from two kinds of permanent magnetic gear is also made.Under the circumstance of steady motion at different speeds,the results including eddy current loss and magnetic torque of the driving and driven wheel of two kinds of permanent magnetic gear are presented.